2017
DOI: 10.1124/mol.116.107136
|View full text |Cite
|
Sign up to set email alerts
|

SH479, a Betulinic Acid Derivative, Ameliorates Experimental Autoimmune Encephalomyelitis by Regulating the T Helper 17/Regulatory T Cell Balance

Abstract: CD4 T helper cells, especially T helper 17 (T17) cells, combined with immune regulatory network dysfunction, play key roles in autoimmune diseases including multiple sclerosis (MS). Betulinic acid (BA), a natural pentacyclic triterpenoid, has been reported to be involved in anti-inflammation, in particular having an inhibitory effect on proinflammatory cytokine interleukin 17 (IL-17) and interferon- (IFN-) production. In this study, we screened BA derivatives and found a BA derivative, SH479, that had a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(72 reference statements)
2
6
0
Order By: Relevance
“…For more explanation, in the context of dementia, the bypassing of Aβ oligomers possibly allows this triterpenoid to limit cell death susceptibility via inhibition of glial cell activation or ROS generation . The potent anti‐inflammatory function of BA (or its derivatives) also specifies its importance on immune‐dependent diseases such as lethal endotoxemia (or Autoimmune Encephalomyelitis) that trigger the levels of TNF‐alpha (increased trend) or IL‐10 (decreased trend) . Many papers are in accordance with the current data and clearly describe a significant increase in TNF‐alpha in the serum or hippocampi in dementia, while quantified IL‐10 levels only represent inconclusive data; although a high expression of hippocampal IL‐10 in AD transgenic mice could demonstrate a potent compensatory mechanism in the immune feedback .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For more explanation, in the context of dementia, the bypassing of Aβ oligomers possibly allows this triterpenoid to limit cell death susceptibility via inhibition of glial cell activation or ROS generation . The potent anti‐inflammatory function of BA (or its derivatives) also specifies its importance on immune‐dependent diseases such as lethal endotoxemia (or Autoimmune Encephalomyelitis) that trigger the levels of TNF‐alpha (increased trend) or IL‐10 (decreased trend) . Many papers are in accordance with the current data and clearly describe a significant increase in TNF‐alpha in the serum or hippocampi in dementia, while quantified IL‐10 levels only represent inconclusive data; although a high expression of hippocampal IL‐10 in AD transgenic mice could demonstrate a potent compensatory mechanism in the immune feedback .…”
Section: Discussionsupporting
confidence: 69%
“…15,40,41 The potent anti-inflammatory function of BA (or its derivatives) also specifies its importance on immune-dependent diseases such as lethal endotoxemia (or Autoimmune Encephalomyelitis) that trigger the levels of TNF-alpha (increased trend) or IL-10 (decreased trend). 42,43 Many papers are in accordance with the current data and clearly describe a significant increase in TNF-alpha in the serum or hippocampi in dementia, while quantified IL-10 levels only represent inconclusive data; although a high expression of hippocampal IL-10 in AD transgenic mice could demonstrate a potent compensatory mechanism in the immune feedback. 34,44,45 Restoring the cholinergic pool through inhibition of AchE and butyrylcholinesterase (BCHE) may provide another possible explanation for the protective effects of BA against AD.…”
Section: Discussionsupporting
confidence: 62%
“…Our group's previous work demonstrated that SH‐479 could ameliorate experimental autoimmune encephalomyelitis (EAE) by promoting the STAT5 signaling pathway and suppressing NF‐κB signaling pathway . SH‐479 also inhibits collagen‐induced arthritis by modulating T‐cell JAK‐STAT pathways .…”
Section: Discussionmentioning
confidence: 99%
“…It had been provided substantial evidence that Th17 cells had significant role in MS. Up-regulation of Th17 cells and IL-17A was observerd in the CNS of MS patients, especially in chronic active lesions and acute lesions [ 16 , 17 ]. More importantly, inhibition of Th17 cell differentiation could significantly ameliorated MOG (35-55)-induced EAE [ 18 , 19 ]. For example, CD226 pAb administration was found to reduced onset of EAE by inhibiting Th1/Th17 production [ 20 ].…”
Section: Discussionmentioning
confidence: 99%